Ionization of pyridine: interplay of orbital relaxation and electron correlation - Trofimov, A.B.; Holland, D.M.P.; Powis, Ivan; Menzies, R.C.; Potts, A.W.; Karlsson, Lennart; Gromov, E.V.; Badsyuk, I.L.; Schirmer, J. (American Institute of Physics, 2017)
The valence shell ionization spectrum of pyridine was studied using the third-order algebraic-diagrammatic construction approximation scheme for the one-particle Green’s function and the outer-valence Green’s function method. The results were used to interpret angle resolved photoelectron spectra recorded with synchrotron radiation in the photon energy range of 17–120 eV. The lowest four states of the pyridine radical cation, namely, 2A2 (1a 2 −1 1a2−1 ), 2A1(7a 1 −1 7a1−1), 2B1(2b 1 −1 2b1−1), and 2B2(5b 2 −1 5b2−1), were studied in detail using various high-level electronic structure calculation methods. The vertical ionization energies were established using the equation-of-motion coupled-cluster approach with single, double, and triple excitations (EOM-IP-CCSDT) and the complete basis set extrapolation technique. Further interpretation of the electronic structure results was accomplished using Dyson orbitals, electron density difference plots, and a second-order perturbation theory treatment for the relaxation energy. Strong orbital relaxation and electron correlation effects were shown to accompany ionization of the 7a1 orbital, which formally represents the nonbonding σ-type nitrogen lone-pair (nσ) orbital. The theoretical work establishes the important roles of the π-system (π-π* excitations) in the screening of the nσ-hole and of the relaxation of the molecular orbitals in the formation of the 7a1(nσ)−1 state. Equilibrium geometric parameters were computed using the MP2 (second-order Møller-Plesset perturbation theory) and CCSD methods, and the harmonic vibrational frequencies were obtained at the MP2 level of theory for the lowest three cation states. The results were used to estimate the adiabatic 0-0 ionization energies, which were then compared to the available experimental and theoretical data. Photoelectron anisotropy parameters and photoionization partial cross sections, derived from the experimental spectra, were compared to predictions obtained with the continuum multiple scattering approach.